Spatial Variation of the Characteristics of Groundwater in the Locality of AL-Amanin the Al-Mahjoub Area – Misurata Using GIS in 2021 (Abhat Journal, 2023)
The research aims to analyses the spatial variation of the characteristics of groundwater in the locality of AL-aman in the Al-Mahjoub area - Misurata, relying on the analysis of 7 samples of groundwater wells in the area in the laboratory, building a geographical database for it, and producing digital maps of pH, electrical conductivity (EC) and total dissolved salts (TDS), and for some negative and positive ions using GIS, The results showed a spatial discrepancy in the distribution of qualitative characteristics between groundwater wells in the study area, where the pH ranged between the highest 7.52 in well 3 and the lowest 6.65 in well 5, while the values of total dissolved salts were between 10418 in well 6 and about 1970 mg / liter in well 7, and with these values, the wells of the study area are outside the permissible limits according to the Libyan and international specifications for domestic drinking use, while Calcium concentrations in groundwater wells reached between 200 and 400 mg/L, the average chloride was between 781 and 4331 mg/L, the results of laboratory analyses indicated that the total hardness values in the water of the wells of the study area reached the highest value of about 2,400 mg/L in the well 6. , and the least amounted to 800 mg / liter in well 7. The water of the study area is considered very hard according to the classification of Sawyer and McGraty, As a summary, the study produced digital maps for the spatial variation of the qualitative characteristics of groundwater in the locality of AL-aman.
Keywords: spatial variance; pH; groundwater; safety locality; geographic information systems